Yield Gaps and Scaling Up of Sesame Variety (RT-351) in Potential Areas of Rajasthan - Meena, Mohar Singh; Singh, S K; Meena, H N; Bishnoi, R (Indian Journal of Extension Education, 2023)
The study evaluates the cluster front line demonstrations (CFLDs) conducted under the national food security mission on sesame (RT-351) by 26 KVKs of Rajasthan state. Four thousand one (4001) partner farmers responded to the study during 2016-2020. The CFLDs were undertaken in a 172.00 ha area in 26 districts during these five years. Yield gaps and technology index were calculated under the study. The result shows an extension gap of 1.35qha-1 and a technology gap of 2.78q/ha. The technology index was found to be 35.11%, while a yield advantage of 36.17% was found in CFLDs. KVKs of Rajasthan state could add Rs.1.45 crores to the income of partner farmers. The improved variety & better extension services significantly enhanced production and productivity. Participatory approaches in the sesame seed supply chain and institutional linkage were critical for scaling up sustainable technology and improving farmers’ access to quality and sufficiently improved seeds. More capsules/ plant and resistance to stem & root rot attracted the farmers. Technical backstopping, supplying of seed, and seed exchange through farmer-to-farmer extension were crucial on a sustainable basis. Regular monitoring by experts and farmers’ feedback is vital for sustained production and productivity improvement of the sesame crop.